Virulence traits and bacterial interactions within the complex microbial population in urinary double-J catheters - Farizano, Juan Vicente; Castagnaro, Emilia; Arroyo-Egea, Julián Thomas; Aparicio, Juan Daniel; Vallejos, Alicia Cecilia; Hebert, Elvira María; Saavedra, Lucila; Rapisarda, Viviana Andrea; Villegas, Josefina María; Grillo-Puertas, Mariana (Frontiers in Microbiology, 2025)
Indwelling devices, such as double-J stents, are commonly used in urological surgery and are often associated with a high risk of urinary tract infections (UTIs) due to biofilm-related complications. In this study, we characterized 27 clinical bacterial isolates from double-J catheters, including Staphylococcus spp., Enterococcus faecalis, Klebsiella pneumoniae, Escherichia coli, and Bacillus spp., to investigate their pathogenic potential. Our findings revealed that strong biofilm producers (E. coli, S. aureus, and B. subtilis) exhibited robust extracellular matrix synthesis. Notably, multidrug resistance was observed in E. coli, K. pneumoniae, and E. faecalis. Mixed-culture experiments demonstrated that Bacillus spp. enhanced the biofilm formation of uropathogens, suggesting a potential impact on clinical outcomes. The characterization of the polymicrobial population colonizing double-J catheters, as conducted in this study, is essential for understanding the complexity and clinical behavior of biofilm-related infections associated with medical devices. Additionally, our results highlight the clinical relevance of underreported genera, such as Bacillus, which are often overlooked in routine clinical diagnostics. Gaining insights into the interaction mechanisms and survival strategies of several bacterial species colonizing double-J catheters may help shift current paradigms in understanding catheter-related infections.